Partial hepatectomy in rats results in immediate down-regulation of p27Kip1 in residual liver tissue by transcriptional and post-translational processes - Rohlfing, Anne-Katrin; Trescher, Karoline; Hähnel, Juliane; Müller, Christian; Hildebrandt, Jan-Peter (Frontiers in Physiology, 2013)
Purpose: The cyclin-dependent kinase (Cdk) inhibitor p27Kip1 may be involved in regulating re-entry of residual hepatocytes into the cell cycle upon loss of liver tissue by partial hepatectomy (PH). As yet, changes in Kip1 expression during the initial period following PH are not well characterized. We investigated immediate changes in Kip1 mRNA and protein levels as well as changes in Kip1 phosphorylation in liver tissue within the relevant time window between surgery and the onset of DNA synthesis at 10-12 h. Methods: We used real-time PCR, quantitative Western blotting and immune histochemistry on tissue samples of adult rats obtained during or between 2 and 10 h after surgical removal of two thirds of the liver to analyze Kip1 mRNA or protein levels, respectively, or to quantify nuclear expression of Kip1. Results: Kip1 mRNA was down-regulated within 4 h after PH by 60 % and remained unchanged thereafter up to 10 h. With a lag phase of 2-3 h, Kip1-protein was downregulated to a level of 40 % of the control. The level of Thr187-phosphorylated Kip1 started to increase at 4 h and reached a maximum level at 8-10 h after PH. Kip1 immunoreactivity was observed in 30 % of the hepatocytes before PH. Within 6-8 h after PH, more than half of the hepatocytes lost nuclear Kip1 signals. Kip1-specific micro-RNAs (miRNA221, miRNA222) were not changed upon PH. Conclusions: A portion of hepatocytes in adult rats constitutively express Kip1 and downregulate Kip1 immediately upon PH. This response involves transcriptional processes (loss of Kip1 mRNA) as well as accelerated degradation of existing protein (increase in pThr187-phosphorylation mediating polyubiquitinylation and proteasomal degradation of Kip1). Kip1 downregulation occurs precisely within the intervall between surgery and onset of DNA synthesis which supports the hypothesis that it mediates activation of G0/S-phase Cdk/cyclin-complexes and re-entry of hepatocytes into the cell cycle.